Formulation self nano emulsifying drug delivery system glimepiride using oleic acid as oil phase - Sani Ega Priani; Nurrayyan Nurrayyan; Fitrianti Darusman (Pharmaciana, 2017)
Glimepiride is a third generation sulphonylurea antidiabetic drug. Glimepiride is poorly water soluble drug that may cause poor dissolution and unpredicted bioavailability. Self nanoemulsifying drug delivery systems (SNEDDS) have become a popular formulation option as nanocarriers for poorly water-soluble drugs. The objective of this research was to develop SNEDDS formulation of glimepiride to improve oral dissolution and bioavailability. Glimepiride SNEDDSÂ  was formulated using oleic acid as oil phase, tween 80 as surfactant, and transcutol as co-surfactant due to their higher solubilization effect. The formulated SNEDDS were evaluated for % transmittance, dispersibility, thermodynamic stability, dissolution, globule size and morphology analysis. The results showed that the glimepiride SNEDDS was rapidly formed clear emulsion and stabile based on thermodynamic test. Transmission electron microscopy demonstrated the spherical droplets morphology in nanometer range. The globule average diameter size was 45 nm. The SNEDDS formulation significantly increase dissolution of glimepiride compared with pure drug.